The Utilization Of Instragram As The Media To Increase Religious Behavior For Student - Dwi Utami, Luh Kadek; Sudarsana, I Ketut; Yuliani, Ni Made; Piartha, I Nyoman (Institut Hindu Dharma Negeri Denpasar, 2019)
Nowadays, People religious behavior has decreased because of misusing information access on social media. It shows the bad influence caused by the existence of social media. However, social media can also be used as a medium to improve human?s religious behavior. The use of instagram as one of the social media product as a tool (education technology) to improve students' religious behavior is done through the project method. The project method that applies the habituation model is done by students by always making a live story on Instagram about the activities they do before going to school, such as praying and saying farewell to parents in a certain period of time. Activities are carried out continuously that will form the character of students who always reflect the commendable behavior that is a form of religious behavior of a person.